Urinary Exosomal Thyroglobulin in Thyroid Cancer Patients With Post-ablative Therapy: A New Biomarker in Thyroid Cancer - Huang, Tse-Ying; Wang, Chih-Yuan; Chen, Kuen-Yuan; Huang, Li-Ting (Frontiers in Endocrinology, 2020)
Background: Most patients with thyroid cancer typically receive thyroidectomy with ablative radioactive iodine therapy. Such patients were followed with thyroid ultrasonography and serial serum thyroglobulin evaluation. Exosomes are nanovesicles secreted into extracellular environments, including plasma, saliva, urine, and other body fluids of patients with cancer. We try to find the early prognostic and exosomal biological markers of urine. Methods: We analyzed urinary exosomal proteins, including thyroglobulin and galectin-3, to identify early prognostic biological markers in urine for patients receiving operation and radioactive iodine ablative therapy. We enrolled sixteen newly diagnosed patients with papillary thyroid carcinoma and follicular thyroid carcinoma. We collect all patient’s urine samples before operation, immediately after operation, post-operatively at three and six months (4 collections per patient). The levels of pre-operative and post-ablative of urinary exosomal thyroglobulin and galectin-3 in patients with thyroid cancer were measured. Results: Trends in urinary thyroglobulin concentrations in patients with post-ablative thyroid cancer were detected in the first sixteen patients. Importantly, serum thyroglobulin was not detected in five patients after operation and radioactive I-131 ablation, while urinary exosomal thyroglobulin still showed an increasing trend, which implicating the probable recurrence of thyroid cancer. This is the first study to evaluate whether urinary exosomal thyroglobulin is a future biological marker as a substitute for serum thyroglobulin. Conclusion: Our study have developed a brand-new evaluation for tracking thyroid cancer. The most useful scenario in using a test that is potentially more sensitive than existing serological testing is to eliminate the suspicion of recurrence and remove subjects from long term follow up.